Agroclimatic Classification of Karnataka (KHARIF Crop Season) According To Hargreaves - Ratnam, B P; Kavi, P S (Annals of Arid Zone, 2016)
The agroclimatic classification of Karnataka was done for kharif cropping season using the weekly rainfall at 70% probability and Penman potential evapotranspiration.In the State arid climate was observed in the eastern part and semi-arid climate in the central region, with a narrow sub-humid zone in the western region and a parallel humid belt to the west of it. The coastal region showed a per-humid climate.